Expectations and conceptions of teachers working in the first years to attend a graduate degree with an interdisciplinary approach (Research, Society and Development, 2022)
This article, with a qualitative approach, investigates the expectations of teachers who work in the early years when they seek a postgraduate course whose pedagogical proposal offered was the approach of mathematics in an interdisciplinary perspective. To do so, it used content analysis based on narratives written in a descriptive memorial, which was one of the items in the selection notice for admission to the graduate course. The corpus of analysis of the collected data involves excerpts from narratives, extracted from descriptive memorials, presented by 12 teachers from the early years of Elementary School. First, from the exploratory reading of the memorials, excerpts were identified that were related to the proposed objectives, making possible a selective reading and from there, the emerging categories were listed, a posteriori. As a result of this research, eight main categories were found, in addition other than the profile of the candidates. The results show that the teachers demonstrate the expectation of being part of a teacher training course, at the postgraduate level, to improve their knowledge and act differently in the classroom based on new learning. Investment in continuing education for teachers in the early years of elementary school is of great importance, considering that the training process does not have an end itself. We realize that they understand it as a continuous process to be developed throughout the professional career, requiring teachers to seek renewal of knowledge, sources and methods continuously.